Smart Environment Program, Smart Way to Smart City - Tutik Rachmawati; Priska Diah Pertiwi (Indonesian Association for Public Administration, 2017)
Bandung City Government is ranked the 3rd in smart city index in Indonesia only within 8 months of smart city application. Considering this achievement, it is necessary to study this fast-tracking success of smart city to enable a lesson learnt for other local governments. Hence, this research aims at evaluating the best practices of smart environment program as one of smart city projects and analyzing the positive transformation being brought. The analysis will be based on three core activities in smart environment: (1) the creation of thematic parks as open public spaces; (2) the restoration and the revitalization of rivers and its river banks; (3) urban gardening or urban farming. Combined with the result of extensive of literature review, this research will apply eight (8) aspects of smart environment. These aspects are (1) The Provision of Public Open Space; (2) Good Waste Management; (3) Slum Areas Management; (4) The Revitalization of River; (5) Eliminate “Chopsticks Syndrome” in Building Construction; (6) Alternative energy; (7) Reducing the Production of CO2; (8) Urban Farming. A qualitative research method were used in this research. The analysis of this research is a comparative analysis, with the use of smart city best practices in other cities in other countries as the benchmark. Seven local government work units/departments/agencies of Bandung Citywhich play important role as the leading sectors of the smart environment program were the key resources of this research. The data were collected from 30 interviews. This research gave its reader a new perspective in understanding the concept and the practices of smart city in the public administration perspective.